Back to the Past: When Segmentation Is More Efficient Than Paging - Laux Jr, Lauri P.; Hexsel, Roberto A. (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2018: Anais do XVII Workshop em Desempenho de Sistemas Computacionais e de ComunicaçãoDO - 10.5753/wperformance.2018.3331, 2018)
Virtual Memory was devised in a time of scarce resources. In the coming decade we expect to see physical memory systems populated with 264 bytes of RAM, a fraction of which may be non-volatile. Demand paging is inefficient in such large memories because space (Page Tables) and time (Page Table walks) overheads are too high. We collected execution traces from six applications and characterized their virtual memory behavior with respect to miss rates in references to Translation Buffers (TLBs) and Segment Buffers (SBs). Our measurements indicate that the miss rates for SBs are 2-3 orders of magnitude smaller than for TLBs. In light of these results, we discuss some of the design implications of segmented systems and of SBs.